Assessing cognitive flexibility in mice using a custom-built touchscreen chamber - Pais, Rui C.; Goldani, Ali; Hutchison, Jayden; Mazrouei, Amirhossein; Khavaninzadeh, Mostafa; Molina, Leonardo A.; Sutherland, Robert J.; Mohajerani, Majid H. (Frontiers in Behavioral Neuroscience, 2025)
Automated touchscreen systems have become increasingly prevalent in rodent model screening. This technology has significantly enhanced cognitive and behavioral assessments in mice and has bridged the translational gap between basic research using rodent models and human clinical research. Our study introduces a custom-built touchscreen operant conditioning chamber powered by a Raspberry Pi and a commercially available computer tablet, which effectively addresses the significant cost barriers traditionally associated with this technology. In order to test our prototype, we decided to train C57BL/6 mice on a visual discrimination serial-reversal task, and both C57BL/6 and AppNL−G−Fstrain - an Alzheimer’s Disease (AD) mouse model - on a new location discrimination serial-reversal task. The results demonstrated a clear progression toward asymptotic performance, particularly in the location discrimination task, which also revealed potential genotype-specific deficits, with AppNL−G−F mice displaying an increase in the average number of errors in the first reversal as well as in perseverative errors, compared to wild-type mice. These results validate the practical utility of our touchscreen apparatus and underline its potential to provide insights into the behavioral and cognitive markers of neurobiological disorders.